Application of pulsed Nd:YAG laser in thin foil microwelding - Ventrella, Vicente Afonso [UNESP]; Berretta, Jose Roberto; Rossi, Wagner de (Inderscience Enterprises Ltd, 2014)
Experimental investigations were carried out using a Nd:YAG laser operating in pulsed mode for welding a lap joint between thin foil and thick sheet. The pulse energy was varied from 1.5 to 3.0 J at increments of 0.25 J with a 4 ms pulse duration. The base material used for this study was AISI 316L foils with 100 mu m thickness and sheet with 3.0 mm thickness. The welds were analysed by optical and electronic microscopy, tensile shear tests and micro hardness. The results indicate that pulse energy control is of considerable importance to join thin foil and thick sheet with good quality. The ultimate tensile strength of the welded joints increased at first and then decreased as the pulse energy increased. The process appeared to be very sensitive to the gap between couples. Large voids delimited by the molten zone boundary were observed in joints welded with high pulse energy.
Keywords: AISI 316L; laser microwelding; Nd:YAG laser; thin foil; stainless steel